DAMPAK KEBIJAKAN FISKAL DAN MONETER DALAM PEREKONOMIAN INDONESIA: APLIKASI MODEL MUNDELL-FLEMING - Teguh Santoso; Maruto Umar Basuki (Jurnal Organisasi dan Manajemen, 2009)
This study aims to analysis the impact of fiscal and monetary policy in Indonesian economy by using Mundell Fleming (IS-LM-BOP) model. The main objective of this paper is to see the impact of fiscal and monetary policy to Indonesia Gross Domestic Product (GDP). Indonesia as a small open economy with imperfectly capital mobility, so temporary thesis of the Mundell-Fleming model is that monetary policy more effective than fiscal policy in improving of the GDP, that caused by its crowding out effect yielded from expansive\ fiscal policy. A variant of the Mundell Fleming model for the Indonesian economy is constructed and analysed using the Two Stage Least Square Methods (2sls). The result of two stage least square estimation indicating that the impact of monetary policy with money supply(M2) instrument is more effective in improving GDP than fiscal policy with government expenditure instrument . This result is proved with influences which are positive and significant among money supply (M2) variable and GDP from demand side. However, goverment expenditure variables give positive effect but not significant to the GDP. These finding support the Hypothesis of model Mundell-Fleming